Work values of millenial interior designer in the Philippines - Tan, Anna Carmela T.
This qualitative study focused on determining the work values evident among selected Millennial Filipino interior designers. It also attempted to analyze the perceptions of interior designers from older generations regarding the values of Millennials and recognize if these values affect their work relationship. Ten (10) Millennial interior designers and ten (10) non-Millennial interior designers from various firms within Metro Manila were interviewed. Grounded Theory was used, so it revolved mainly around the existing secondary data on Millennial, Filipino, and interior designer work values, and on the work values gathered from this study. A qualitative research design was used and convenience sampling was employed in selecting the participants. The Millennial respondents had to be born within the years 1980 to 2000, while the non-Millennial respondents had to be born from 1979 or older. The respondents from older generations were from the Baby Boomer Generation and Generation X. Interview questionnaires and an audio recorder were used to gather data. Content analysis was used to connect the responses with the secondary data initially gathered by the researcher. The results showed that Millennial Filipino interior designers gave more importance to intrinsic values; such as professional growth and learning. They exhibit high power distance, do not show loyalty to their organizations, work well in teams but prefer working alone, prefer to have open communication, value recognition, appreciate mentorship, focus on work-life balance, are committed to their work, and are media savvy. The interview responses from the older generation showed that their main issues with the younger generation include tendency to hop from one organization to another and the dependence on technology and the internet. These somehow affect their trust, their willingness to mentor, and their regard towards their Millennial colleagues.